The PENGARUH LAMA USAHA DAN SKALA USAHA TERHADAP KEBERHASILAN USAHA DENGAN PENGGUNAAN INFORMASI AKUNTANSISEBAGAI VARIABEL INTERVENING TAHUN 2020 – 2021 - Muhammad Faqih Riansyah; Sari Andayani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
UMKM are one of the business activities that can make a considerable contribution to state income and employment for the people in Indonesia. This study aims to prove whether the length of the business and the scale of the business affect the success of the business through the use of accounting information at bookstores in Surabaya. The population during 2020-2021 was 246 umkm’s bookstore in Surabaya. The determination of this sample uses a simple random sampling technique. The data used are primary data and secondary data. The results are that the length of the business has a positive effect and the scale of the business has a significant effect on the use of accounting information. the length of the business has a positive effect and the scale of the business does not have a significant positive effect on the success of the business. The use of accounting information has a significant positive effect on the success of the business. The variable of using accounting information is proven to be an intervening variable among the variable of business length and variable of business scale with business success. In other words, business experience affects business success through the use of accounting information